2015
DOI: 10.3945/jn.114.208595
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation in the Small Intestine Contributes Substantially to Intestinal Starch Disappearance in Calves ,

Abstract: Fermentation, rather than enzymatic digestion, is the main reason for small intestinal starch disappearance in milk-fed calves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
2
34
1
Order By: Relevance
“…A reduced affinity of lipase to its substrate may result in an increase in the hydrolysis of added substrate and therefore be recorded as increased activity. The decreased apparent total tract protein digestibility and increased passage rate when feeding GSC suggest that starch was fermented, and starch fermentation in both the large and small intestine was indeed confirmed by Gilbert et al (2015a). From the current study, replacing lactose with GCS in the MR increased α-amylase activity, potentially by adaptation to the starch as reviewed by Brannon (1990) and Mosenthin and Sauer (1993) or by inducing microbial amylase activity (Cummings and Macfarlane, 1991).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…A reduced affinity of lipase to its substrate may result in an increase in the hydrolysis of added substrate and therefore be recorded as increased activity. The decreased apparent total tract protein digestibility and increased passage rate when feeding GSC suggest that starch was fermented, and starch fermentation in both the large and small intestine was indeed confirmed by Gilbert et al (2015a). From the current study, replacing lactose with GCS in the MR increased α-amylase activity, potentially by adaptation to the starch as reviewed by Brannon (1990) and Mosenthin and Sauer (1993) or by inducing microbial amylase activity (Cummings and Macfarlane, 1991).…”
Section: Discussionmentioning
confidence: 50%
“…In addition, total tract fermentation of GCS was quantified, which averaged 447 ± 27 g/day, corresponding to 89% of intake. By difference, this indicated that 54% of the GCS intake was fermented before the terminal ileum (Gilbert et al, 2015a).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Applying this processing treatment to SBM and RSM significantly reduced the SID and ATTD of CP in growing pigs (Chapters 2 and 3). With regard to starch, calves had a lower level of digestive enzymes compared with pigs and starch mainly disappeared from the small intestine through bacterial fermentation rather than enzymatic digestion (Gilbert et al, 2015). Moreover, ruminal fermentation in dairy cows seemed to affect the lignosulfonate and heat-treated ingredient in such a way that it became accessible for bacterial fermentation in the small intestine.…”
Section: Model Processing Treatmentmentioning
confidence: 99%